Analysis on Composite Erosion Process Based on Multi Dynamic Erosion Environment Simulation. Issue 1 (June 2020) - Yang, Chunxia; Zhen, Bin; Zhang, Pan; Xiao, Peiqing
Abstract: Using the compound erosion experimental device developed by ourselves, the compound erosion process simulation experiment of 35° steep slope were carried out under different combination modes of freeze-thaw, wind, rainfall. The runoff and sediment yield change process of Pisha sandstone slope under different dynamic combination environment were studied. The results show that the superposition of wind, freeze-thaw and rainfall conditions obviously promotes the occurrence of slope erosion, among which the effect of freeze-thaw increased the collapse phenomenon obviously in the erosion process.